JAM’IYAH SHOLAWAT SERIBU REBANA DI JOMBANG TAHUN 2010-2018 - Indah Nurrohmatul Inayah (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
Abstract: The existence of Jam'iyah Sholawat Seribu Rebana continues to exist and spread its wings in the midst of Jombang society, which is a unique social phenomenon to be studied. This article aims to explore Jam'iyah Sholawat Seribu Rebana in Jombang Regency from a historical diachronic point of view. This search uses historical research methods with a sociological approach. The theory used in the analysis is John Obert Voll's theory of Continuity and Change. The results of this search are summed up into three points. First, the establishment of Jam'iyah Sholawat Seribu Rebana, which was triggered at the 100th anniversary of the death of the Indonesian professor, Gus Dur, in 2010 under the tutelage of KH. Nur Hadi. Second, the development of the Jam'iyah Sholawat Seribu Rebana from 2010-2018 has progressed very rapidly, starting from the development of the activity program, increasing the number of members and the spread of the Jam'iyah Sholawat Seribu Rebana area to the area around Jombang Regency. Third, the views of the Jombang people regarding the development of Jam'iyah Sholawat Seribu Rebana all responded positively, accompanied by several important notes. Keywords: history, development of Jam'iyah Sholawat Seribu Rebana, Jombang